Smart Urban Farming 5.0: Integration of Vertical Farming Automation and Solar Panels for Maximum Energy Efficiency and Productivity in Major Cities in Indonesia - Farhan Zikri (Agriculture Journal, 2024)
This study explores the development of Smart Urban Farming 5.0 as an innovative solution to address energy efficiency and food security challenges in Indonesia’s major urban centers. The research is driven by rapid urbanization, which limits agricultural land and increases the need for space- and energy-efficient farming systems. The main objective is to design and evaluate the integration of solar panels with automated vertical farming to enhance agricultural productivity while reducing reliance on conventional electricity sources. The methodology includes building an IoT- and AI-based automated farming prototype powered by solar energy, and testing its performance over three months by monitoring energy consumption, plant growth, and harvest quality. The results reveal a significant reduction in operational costs, a 62% decrease in traditional electricity usage, and a 28% increase in crop yields compared to conventional systems. While the system requires technical training, user feedback indicates high acceptance. Overall, Smart Urban Farming 5.0 proves to be a viable and effective approach for sustainable urban agriculture, contributing to clean energy and food-related Sustainable Development Goals (SDGs). This research opens pathways for future advancements in intelligent and environmentally friendly urban farming technologies.